Exploring health locus of control among vaccine-hesitant parents: a scoping review - Chiara Lorini; Guglielmo Bonaccorsi; Laura Rasero; Loredana De Marchis; Yari Longobucco; Khadija El Aoufy; Paolo Iovino; Patrizio Zanobini; Emanuele Buccione; Camilla Elena Magi; Stefano Bambi; Antonio Bonacaro; et al. (BMJ Open)
Objectives This scoping review aimed to explore the relationship between health locus of control (HLOC) and vaccine hesitancy among parents of children aged 0–18 years, focusing on the tools and methods used to assess these constructs.Design The review followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines and adhered to established methodologies for scoping reviews, including systematic searches across four electronic databases.Data sources PubMed, PsycINFO, Web of Science and CINAHL were searched using a comprehensive search strategy to identify relevant studies on 24 September 2024.Eligibility criteria for selecting studies Studies were included if they examined HLOC and vaccine hesitancy in parents, measured these constructs with validated tools and focused on childhood vaccination.Data extraction and synthesis Data were extracted into a structured table capturing study characteristics, HLOC and vaccine hesitancy measurements, and key findings. Results were synthesised narratively to highlight associations and patterns.Results Five studies involving a total of 11 758 parents and caregivers of children aged 0–18 years met inclusion criteria. Higher internal HLOC was consistently associated with lower vaccine hesitancy and higher compliance, while lower chance HLOC correlated with greater hesitancy. Powerful others HLOC (ie, trust in healthcare professionals) emerged as a key predictor of better vaccine adherence.Conclusions The findings suggest that internal HLOC and trust in healthcare providers are predictors of vaccine acceptance among parents. However, standardised tools and longitudinal studies are needed to further elucidate these relationships and inform targeted interventions to reduce vaccine hesitancy.